2022
DOI: 10.3389/fpsyg.2021.768293
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Cheating Behavior: The Mediating Effects of Organizational Identification and Perceived Supervisor Moral Decoupling

Abstract: Previous corporate social responsibility (CSR) studies at the employee level have focused on the influence of CSR on employees’ positive attitudes and behavior. However, little attention has been paid to the relationship between CSR and unethical behavior and the underlying mechanism. Based on social information processing theory, this study investigates how CSR affects employee cheating via employees’ organizational identification and perceived supervisor moral decoupling. Additionally, this study discusses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 111 publications
0
1
0
Order By: Relevance
“…When an organization engages in altruistic, other-serving behaviors to fulfill its social obligations for the greater good, the organization appears more socially attractive and desirable. This increased attractiveness reinforces employees' identification with their organizations, which echoed the existing literature on the relationship between organizational attractiveness and employee identification [40,42,78,80]. Internally, employees improve their self-concept by feeling proud that their organizations have contributed to the well-being of society, resulting in stronger organizational identification.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…When an organization engages in altruistic, other-serving behaviors to fulfill its social obligations for the greater good, the organization appears more socially attractive and desirable. This increased attractiveness reinforces employees' identification with their organizations, which echoed the existing literature on the relationship between organizational attractiveness and employee identification [40,42,78,80]. Internally, employees improve their self-concept by feeling proud that their organizations have contributed to the well-being of society, resulting in stronger organizational identification.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies [33,77,78] have shown that employees display stronger OI when their organizations are involved in CSR activities. The association between CSR perceptions and organizational identification is rooted in social identity theory [24].…”
Section: Connecting Csr Motives To Organizational Identificationmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, studies have indicated a positive relation between temptation (Pate, 2018), COVID-19 (Hillebrandt & Annika, 2022), underdog expectation (Loi et al, 2021), customer mistreatment (Men et al, 2021), peer influence (Malesky et al, 2022), performance pressure (Mitchell et al, 2018) and cheating behavior. Concomitantly, prior work has suggested a negative relation between corporate social responsibility and cheating behavior (Luan et al, 2021).…”
mentioning
confidence: 96%